Brain Metastases - Raizer, Jeffrey J.; Abrey, Lauren E.; SpringerLink (Online service) (New York, NY : Springer US : Imprint: Springer, 2007)
Brain metastases are the most dreaded complication of systemic cancer, affecting approximately 170,000 people a year, a far greater incidence than primary brain tumors. Advances in modern chemotherapy have led to an improved control of system cancers, often with agents that poorly penetrate the central nervous system, resulting in an increasing incidence of brain metastases. Traditional chemotherapy has had little impact on brain metastases. The main therapeutic option is radiation therapy, and in a small number of patients - surgery. However, refinements in all of these treatments offer some positive outcomes and an increased ability to stratify patients based on certain criteria. This book will bring current information on the presentation and management of patients with brain metastases, providing available data, giving guidelines that can be applied in day to day practice, updated information for neuro-surgeons, radiation oncologists, medical oncologists, and neuro-oncologists, as well as an overview for physicians in training. "Brain metastases are one of the most devasting consequences of cancer. This text addresses the epidemiology, pathophysiology, imaging, and management of this complication. Experts in the field cover a broad array of relevant topics highlighting the challenges and current therapeutic strategies." Steven T. Rosen, M.D. Series Editor.
Brain Metastases: Epidemiology and Pathophysiology -- The Economics of Brain Metastases -- Neuroimaging of Parenchymal Brain Metastases -- Symptom Management and Supportive Care of the Patient With Brain Metastases -- Surgery for Brain Metastases -- Radiation for Brain Metastases -- Dural and Skull Base Metastases -- Pediatric Brain Metastasis from Extraneural Malignancies: A Review -- Brain Metastases in Hematologic Malignancies -- Chemotherapy for Brain Metastases: Breast, Gynecologic and Non-Melanoma Skin Malignancies -- Chemotherapy for Brain Metastases due to Lung Cancer and Melanoma -- Palliative Care for Patients With Brain Metastases.
Keywords: Oncology .; Surgical oncology; Neurosurgery; Oncology; Surgical Oncology; Neurosurgery